Assessment of heavy metal exposure risk to aquatic birds in the key wetland habitats of the Yellow River (China), using an integrated model - Jian Ding; Ni Wang; Yaqiao Lian; Qian Li; Xinran Li; Fei Yu (Global Ecology and Conservation)
Heavy metal pollution poses a growing threat to wetland ecosystems, impacting their structure and function. Chenqiao Wetland and Qinglong Lake (Henan, China), key bird habitats in the middle and lower reaches of the Yellow River, were analyzed for heavy metal contamination. We assessed the exposure risks of heavy metals (Cu, Cd, Pb, Cr, and Zn) to aquatic birds using an integrated model that considered multiple intake variables: soil intake rate (Is), water intake rate (Iw), plant intake rate (Idf), and prey items intake rate (aquatic animals, Idf). Results revealed significant variation in heavy metal pollution across sampling points, with Cd presenting the highest potential ecological risk in soil. Bioaccumulation coefficients were notably higher in benthic invertebrates compared with fish. Omnivorous and herbivorous birds exhibited significantly higher heavy metal exposure doses (Ej) than carnivorous birds, with the exception of Cr. Among all elements, Zn exhibited the highest Ej, while Pb and Cr posed a high exposure risk (hazard quotient [HQ] > 2) across both food and soil pathways in both omnivorous and herbivorous aquatic birds, which were predominantly exposed to Cu, Zn, Pb, and Cr through plants rather than soil. Conversely, the high Cr HQ in omnivorous and carnivorous birds was primarily associated with the consumption of aquatic animals. This study highlights the importance of considering both food and soil pathways when assessing heavy metal exposure risks in aquatic birds. These findings provide valuable insights for developing strategies to mitigate heavy metal pollution in wetland ecosystems and protect bird populations.